Study of the German-Spanish translation of neologisms related to sustainable tourism - Montes Sánchez, Alba (Estudios de Traducción, 2022)
Sustainable tourism contributes to achieving, directly or indirectly, the 2030 Agenda for Sustainable Development, such as inclusive and sustainable economic growth, sustainable use of the oceans and marine resources, or sustainable consumption and production, among others. Moreover, in our country, tourism is one of the main sources of income and, in order to maintain this location or improve positions in the sector, quality tourism must be offered, with quality products and, consequently, with quality multilingual information. This paper focuses on the importance of analysing and translating neologisms in order to commercialise sustainable development tourism activities. For this, contexts from institutional texts related to sustainable tourism are analysed contrastively in German and Spanish in order to determine the emerging translation difficulties during the transfer to our target language. Finally, a series of conclusions will be presented on the lexical creation and translation of this tourism in Spain, a country committed to the environment and autochthonous culture.